Anti-cancer effects of 1’S-1’-acetoxychavicol acetate and its hemi-synthetic analogues on cancer cell lines / Liew Su Ki - Liew , Su Ki (2018)
1’S-1’-acetoxychavicol acetate (ACA) is a phenylpropanoid isolated from the rhizome of the wild ginger plant, Alpinia conchigera (Zingiberaceae). Nine analogues of ACA were hemi-synthesised and evaluated for their cytotoxic effects using MTT assay against breast, bladder, prostate, oral and liver human cancer cell lines. Only ACA and two analogues, 1’-acetoxyeugenol acetate (AEA) and 1’-acetoxy-3,5-dimethoxychavicol acetate (AMCA) showed significant cytotoxic effects. The aims of the research were to investigate if ACA and its two analogues, first, could exert anti-cancer effects via the proteasome and second, to explore the possible underlying mechanism of action as well as the structure-activity relationship (SAR) involving anti-proliferation, apoptosis induction and anti-migration effects in breast cancer cells. Since the ubiquitin-proteasome system (UPS) is seen as an effective system in modulating tumour cell proliferation, the proteasome-inhibitory potential of ACA, AEA and AMCA was investigated. Among the three different proteasome activities, the best inhibition by these three compounds was the chymotrypsin-like activity of 26S proteasome in MDA-MB-231 breast cancer cells. The docking analysis showed that 1’-acetoxy group is the key player of proteasome inhibition. However, the compounds were significantly less active compared to the commercial proteasome inhibitor, epoxomicin. This suggested that ACA and its analogues did not exert effective anti-cancer effects via the UPS system. However, ACA and its two analogues, AEA and AMCA inhibited the cell growth of MDA-MB-231 breast cancer cells significantly. The 1’- and 4-acetoxy, and methoxy group substituted at 3-position of the benzene ring were found to be important for anti-proliferation, whereas 4-hydroxy, methoxy group at 4- and 5-positions reduced the activity. Further investigation of these three compounds using DNA fragmentation assay showed that they markedly increased apoptosis of MDA-MB-231 cells. The expression levels of cleaved PARP, p53 and Bax were elevated whereas the expression of Bcl-2 and Bcl-xL were decreased after the treatment of ACA, AEA and AMCA. These findings suggested that ACA and the two analogues are able to inhibit MDA-MB-231 cell growth by inducing apoptosis via the mitochondrial apoptotic pathway. Also, the SAR between ACA and its analogues in anti-migration effects were analysed since ACA, AEA and AMCA effectively inhibited the migration of MDA-MB-231 cells. The structural requirements for anti-migration effects are the 1’- and 4-acetoxy, and 3-methoxy groups that were identified as essential for inhibition of the cancer cells migration. In contrast, the 4-hydroxy and 5-methoxy weaken the activity. The compounds also downregulated the expression level of pFAK/FAK, pAkt/Akt via the integrin β1-mediated signalling pathway. Collectively, ACA, AEA and AMCA are potentially beneficial anti-cancer agents by their ability to suppress growth, induce apoptosis and inhibit the migration of breast cancer cells.